1999
DOI: 10.1042/bj3400745
|View full text |Cite
|
Sign up to set email alerts
|

Autoinhibition of neuronal nitric oxide synthase: distinct effects of reactive nitrogen and oxygen species on enzyme activity

Abstract: Nitric oxide (NO) synthases (NOSs), which catalyse the oxidation of -arginine to -citrulline and an oxide of nitrogen, possibly NO or nitroxyl (NO − ), are subject to autoinhibition by a mechanism that has yet to be fully elucidated. In the present study we investigated the actions of NO and other NOS-derived products as possible autoregulators of enzyme activity. With the use of purified NOS-I, -arginine turnover was found to operate initially at V max (0-15 min, phase I) although, despite the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 48 publications
(69 reference statements)
2
2
0
Order By: Relevance
“…To explore the mechanisms underlying TGD in regulation of NO production, we examined the effect of TGD on TNOS enzymatic activity using a commercial kit. Our results exhibited that H 2 O 2 treatment (500 μM, 3 h) significantly suppressed TNOS activity, which was consistent with a previous report ( Kotsonis et al, 1999 ), while TGD treatment not only significantly up-regulated TNOS activity but also effectively restored the H 2 O 2 -suppressed TNOS activity ( Figure 3A ), indicating TGD regulates TNOS activity. Consistently, treatment with L-NAME, an inhibitor of TNOS activity ( Pfeiffer et al, 1996 ), significantly lowered the TGD-induced NO levels, compared with the TGD-treatment group ( Figure 3B ).…”
Section: Resultssupporting
confidence: 93%
“…To explore the mechanisms underlying TGD in regulation of NO production, we examined the effect of TGD on TNOS enzymatic activity using a commercial kit. Our results exhibited that H 2 O 2 treatment (500 μM, 3 h) significantly suppressed TNOS activity, which was consistent with a previous report ( Kotsonis et al, 1999 ), while TGD treatment not only significantly up-regulated TNOS activity but also effectively restored the H 2 O 2 -suppressed TNOS activity ( Figure 3A ), indicating TGD regulates TNOS activity. Consistently, treatment with L-NAME, an inhibitor of TNOS activity ( Pfeiffer et al, 1996 ), significantly lowered the TGD-induced NO levels, compared with the TGD-treatment group ( Figure 3B ).…”
Section: Resultssupporting
confidence: 93%
“…Since HNO may be synthesized during the NOScatalyzed oxidation of L-arginine under certain cofactor conditions (Adak et al, 2000), the inhibition of NOS by HNO may be another pathway of NOS auto inhibition. Kotsonis et al showed that low concentrations of HNO and NO decrease the activity of neuronal NOS (nNOS or NOS-1) purified from pig cerebellum (Kotsonis et al, 1999). We extend this conclusion by showing that both compounds were effective even in retinal homogenates.…”
Section: Discussionsupporting
confidence: 72%
“…-independent NOS (iNOS) in the tissue exists (Lukácová et al 2006). The main mechanism, which could contribute to a decrease of nNOS expression, are (1) autoinhibition of the nNOS activity caused by an excessive formation of NO resulting from iNOS expression, and/or (2) a biological feedback control mechanism by which excessively generated NO can regulate the amount of subsequent NO synthesis (Kotsonis et al 1999). Many other factors, such as the absence of L-arginine, NADPH, FAD and oxygen, and/or the cofactor tetrahydrobiopterin (Marletta 1993;Xia et al 1996) can also contribute to the loss of enzyme expression during ischemia and longer time of reperfusion.…”
Section: Discussionmentioning
confidence: 99%